PENGARUH BERBAGAI MACAM SUMBER BAHAN ORGANIK UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN JAGUNG DI LAHAN PASIR PANTAI SAMAS - Rizki Fajar Audi (FP AGRO 16 UMY 013, 2016)
The research, entitled The Effect of Various Sources of Organic Matter to Increase The Growth And Yield of Corn In Samas Coastal Land was conducted from December up to April 2016 in Samas coastal land, Bantul, Yogyakarta. The research was arranged in Randomized Completely Block Design (RCBD) consisting of 3 treatments. The treatments were: P1: 6,504 tons/ hectare rice straw compost P2: 2,395 tons/hectare gamal leaves compost P3: 11,428 tons/hectare blotong compost. Each treatment was replicated 4 times and consisted of 5 samples per replication. The results showed that the application of rice straw compost with dose of 6,504 tons per hectare can increase vegetative growth of corn and tends increase corn yield than the other treatments. Keywords: various sources of organic matter, compost, corn, Samas coastal land